Drawing the line on physician-assisted death. Issue 3 (21st November 2018) - Jansen, Lynn A; Wall, Steven; Miller, Franklin G
Abstract : Drawing the line on physician assistance in physician-assisted death (PAD) continues to be a contentious issue in many legal jurisdictions across the USA, Canada and Europe. PAD is a medical practice that occurs when physicians either prescribe or administer lethal medication to their patients. As more legal jurisdictions establish PAD for at least some class of patients, the question of the proper scope of this practice has become pressing. This paper presents an argument for restricting PAD to the terminally ill that can be accepted by defenders as well as critics of PAD for the terminally ill. The argument appeals to fairness-based paternalism and the social meaning of medical practice. These two considerations interact in various ways, as the paper explains. The right way to think about the social meaning of medical practice bears on fair paternalism as it relates to PAD and vice versa. The paper contends that these considerations have substantial force when directed against proposals to extend PAD to non-terminally ill patients, but considerably less force when directed against PAD for the terminally ill. The paper pays special attention to the case of non-terminally ill patients who suffer from treatment-resistant depression, as these patients present a potentially strong case for extending PAD beyond the terminally ill.